Implementasi Community Language Learning untuk Meningkatkan Maharah Kalam Siswa Madrasah Aliyah - Alfi, Solehah Widini; Mizan, Ahmad Nur; Zulhannan, Zulhannan (Penerbit Widina, Widina Media Utama, 2025)
The teaching of Arabic at the Madrasah Aliyah level often faces challenges in mastering maharah kalam or speaking skills. Maharoh kalam, in terms of language, is equivalent to the term